2018
DOI: 10.15406/smdij.2018.02.00046
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of morningness-eveningness questionnaire score to ferritin, gamma glutamyl-transpeptidase and alanine amino-transferase concentrations in a large cohort

Abstract: Background: The circadian rhythms of sleep propensity and melatonin secretion are driven by the suprachiasmatic nuclei (SCN) of the hypothalamus. The liver is also considered as an extra-SCN pacemaker and its biological parameters have proved to follow a circadian pattern of secretion. Only one study in the literature was found to investigate the relation between liver biomarkers and Morningness-Eveningness traits, revealing higher levels of ALAT in evening type patients among diabetic subjects. 1 There is cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Furthermore, a study conducted by Wolide et al 18 in Ethiopia reported higher ferritin, waist circumference, BMI, and blood pressure values in patients with type 2 DM, and a strongly significant difference to the control group (p<0.0001). In a cohort study conducted by Cugy et al 19 In France, a significant relationship was reported between serum ferritin levels and elevated liver enzymes and hepatic inflammatory markers (ALT, AST, GGT). In the present study, no significant difference in ALT levels, as one of the hepatic enzymes, was found between the diabetic group and the nondiabetic group.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, a study conducted by Wolide et al 18 in Ethiopia reported higher ferritin, waist circumference, BMI, and blood pressure values in patients with type 2 DM, and a strongly significant difference to the control group (p<0.0001). In a cohort study conducted by Cugy et al 19 In France, a significant relationship was reported between serum ferritin levels and elevated liver enzymes and hepatic inflammatory markers (ALT, AST, GGT). In the present study, no significant difference in ALT levels, as one of the hepatic enzymes, was found between the diabetic group and the nondiabetic group.…”
Section: Discussionmentioning
confidence: 93%